2016
DOI: 10.1080/03075079.2016.1198894
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chinese students’ experience of curriculum internationalisation: a comparative study of Scotland and Australia

Abstract: Increasing enrolment of Chinese students has become a key feature of internationalisation for Western universities, but there is limited research into how curriculum internationalisation affects Chinese students' learning experiences. Using the typologies of curriculum internationalisation (Edwards et al, 2003) as a framework, this paper explores and compares how Scottish and Australian universities integrate international and intercultural elements into their curriculum to support Chinese postgraduate taught … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Hao et al.’s (2016) finding that graduates from overseas institutions did have high expectations of securing high salary packages for their first job. Cheng et al. (2018) argued that Chinese students who studied in China had easier access to work experience through internships or placements compared to Australian- or United Kingdom-educated Chinese international students.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hao et al.’s (2016) finding that graduates from overseas institutions did have high expectations of securing high salary packages for their first job. Cheng et al. (2018) argued that Chinese students who studied in China had easier access to work experience through internships or placements compared to Australian- or United Kingdom-educated Chinese international students.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese international graduates have invested in gaining an Australian higher education degree and, in return, this investment has, over time, yielded positive outcomes in gaining international professional skills and knowledge that allow them to develop their careers in China's competitive labour market (Cheng et al, 2018;J. Hao & Liu, 2017;J.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, it is stated that curriculum internationalization or internationalization of education is vital as it allows students to come across diverse norms and cultures that would shape their overall learning experience and enhance intercultural competence (Cheng et al, 2018;Wang et al, 2012). Curriculum internationalization refers to the inclusion of international and intercultural elements into the subject matter of the curriculum as well as the philosophy and knowledge procedures and support services of a course of study (Leask, 2009).…”
Section: H2: There Is a Positive Relationship Between Mainstream Social Connectedness And Culturalmentioning
confidence: 99%
“…Zimitat’s (2008) survey of undergraduate students in one university, which had undertaken a strategic commitment to IoC, found that approximately half did not recognize an “international dimension to their experiences” when this was offered. On the contrary, several studies show that international students experience apparently internationalized curriculum as parochial, dominated by “western knowledge,” and lacking relevance, in a range of countries including Malaysia (Pandian, Balraj Baboo, & Mahfoodh, 2016), Australia, and Scotland (Cheng, Adekola, Shah, & Valyrakis, 2018). Cheng et al’s comparative study between Australia and Scotland found a “mismatch between academics’ and students’ understandings of curriculum internationalization” (p. 754).…”
Section: Rethinking Student Engagement In Global Learningmentioning
confidence: 99%